A repeat positioning, scanning tunneling microscope based on a straight-push piezoelectric nanopositioner. (25th May 2021) - Guo, Wenjing; Wang, Jihao; Xia, Zhigang; Zhang, Jingjing; Lu, Qingyou
Abstract: In this paper, we develop a repeat positioning, scanning tunneling microscope (STM), whose core component is a new straight-push piezoelectric nanopositioner. The special rigid frame structure and straight-push stepping method of this nanopositioner ensure that there is no lateral deviation while it is stepping. It has a smaller volume and a lower driving voltage than that of traditional piezoelectric nanopositioners with the same load capacity. The test results show that its threshold voltage is only 4 V. Additionally, when the driving signal frequency is constant, its step size and the amplitude of the driving signal show a linear relationship. Moreover, when the driving signal amplitude is constant, the velocity and driving signal frequency of the nanopositioner also show a linear relationship. In addition, the small STM (diameter less than 10 mm, length less than 50 mm) designed on the basis of this nanopositioner can work at full low-voltage. The STM's high-resolution images and repeatable positioning performance are demonstrated in detail in this article. When the STM moves back and forth along the Z direction at a millimeter-scale distance, its positioning deviation in the same area of the sample is less than 30 nm. The capacity of the STM is very important for tracking and observing the different characteristics of some samples in different test conditions and is also significant for applications such as multi-tip collaborative work.